THE EFFECT OF SERVICE QUALITY AND DOCTOR COMPETENCE ON PATIENT SATISFACTION MEDIATED BY THE IMAGE OF ROSELA HOSPITAL - Ester Rita; Hery Winoto Tj; Eka Desy Purnama (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Background: Digital transformation in the health sector requires hospitals to carry out continuous innovation to improve service standards. Rosela Hospital faces the challenge of patient satisfaction levels that have not reached the minimum standard of the Ministry of Health of 95%. Objective: To analyze the effect of service quality and doctor competence on patient satisfaction with hospital image as a mediating variable. Method: Associative quantitative research using the SEM-PLS approach with a sample of 150 outpatient, emergency room, and inpatient respondents. The research instrument used a structured questionnaire with a five-point Likert scale. Results: All hypotheses were accepted with a significance of p <0.05. Service quality has a positive effect on hospital image (β = 0.426; t = 5.493) and patient satisfaction (β = 0.172; t = 2.213). Doctor competence has a positive effect on hospital image (β = 0.535; t = 7.318) and patient satisfaction (β = 0.225; t = 3.067). Hospital image has a positive effect on patient satisfaction (β=0.538; t=5.323) and acts as a partial mediator with a coefficient of 0.229 for the service quality pathway and 0.288 for the doctor's competence pathway. Conclusion: The structural model shows an explanatory power of 77.2% for patient satisfaction, indicating the importance of simultaneous optimization of service quality and doctor's competence through strengthening institutional image.